The Impact of Linguistic Imperialism on Indigenous Languages in Iraq: A Case Study of Language Policy and Preservation - Hadi , Hussam Aldeen Nidhal (Randwick International of Education and Linguistics Science Journal, 2025)
The present study looked into the effects of linguistic imperialism, specifically, the dominance of English, on the preservation and revitalization of indigenous languages in Iraq. Tapping into a phenomenological study, using interviews, the study recruited 30 students enrolled at a university in Baghdad, majoring in different fields of study. Half of the participants were Assyrian and half were Armenian native speakers, with an age range of 20-22 years old and equal numbers of male and female. Thematic analysis was used to analyze the data through open, axial, and selective coding. The linguistic imperialism has impacted Assyrian and Armenian languages in Iraq in a very complex manner. These villages are resistant, and through different cultural activities or family traditions, they try to keep their languages alive; however, the prevalence of English in schools makes the young generation feel displaced. This is the pressure that makes them give more importance to English, leading to lesser exposure and fluency in Assyrian and Armenian-especially now, when the education system is giving more emphasis to English, besides Arabic. The given study underlines urgent policy changes to be made for the promotion and support of indigenous languages in Iraq. The current policies need a re-evaluation in order to keep the life preserved, which gives priority to Arabic and English. Inclusion of indigenous languages into education, resource allocation for learning a language, and the use of social media for revitalization are the crucial steps toward preserving these treasures.